Willingness to pay for rehabilitation of Ibadan urban environment through reforestation projects (2002)
This study was carried out to determine the estimated value of the environmental service functions of the forests of the Ibadan metropolis. It employed the payment card format -Contingent Valuation approach - to elicit willingness to pay (WTP) for environmental rehabilitation of the Ibadan metropolis through reforestation projects, and to investigate the extent to which socio-economic factors influence the WTP. Data were obtained from a multi-stage randomly sampled 370 residents within the five local government areas of the metropolis. The results show that 77% of the respondents were willing to pay various amounts ranging from N50-N500 monthly, NlOO being the modal value, having recorded a 52% response. The mean monthly WP value is N161, resulting in an aggregate estimated value of Ibadan urban forests’ environmental service functions, ranging between N185 468 586 and N240 868 294 (US$1 = NlOO). The reduced model of the double log regression equation revealed the respondents’ employment status and proximity to the urban forest reserves as the only socio-economic variables that significantly influenced WTP. The differences in the mean WTP values within each independent socio-economic variable were not significant (p > 0.05). The results of this study show that there is a need for social valuation of forestry and non-forestry projects that have to do with conversion of forest lands, as a panacea for uncontrolled deforestation.